2003
DOI: 10.1159/000070546
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the H63D and C282Y Mutations in the HFE Gene in 3,015 Blood Donors from Southwestern Germany

Abstract: Background: Hereditary haemochromatosis (HH) is the most common genetic disease with a prevalence of 1:200–1:400 in Northern Europe. In most cases HH is caused by two mutations of the HFE gene (H63D and C282Y). As haemochromatosis leads to elevated iron uptake it is conceivable that blood donors with HFE mutation might be refused from giving a donation less often than donors without the mutation. Therefore, HFE mutations might be overrepresented among frequent blood donors. This study aimed to determine the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 14 publications
1
4
0
Order By: Relevance
“…However, even in the large population of donors studied here, the prevalence of donors with HFE mutations was not different among the high intensity and lower intensity donors. This finding is consistent with previously published studies of smaller numbers of donors (Konig et al, 2003;Boulton et al, 2000) and confirms that it is unlikely that these mutations are responsible for potential genetic contributions to the ability of high intensity donors to repeatedly donate blood without developing iron deficiency anaemia. Another mutation studied in RISE is TF G227S.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…However, even in the large population of donors studied here, the prevalence of donors with HFE mutations was not different among the high intensity and lower intensity donors. This finding is consistent with previously published studies of smaller numbers of donors (Konig et al, 2003;Boulton et al, 2000) and confirms that it is unlikely that these mutations are responsible for potential genetic contributions to the ability of high intensity donors to repeatedly donate blood without developing iron deficiency anaemia. Another mutation studied in RISE is TF G227S.…”
Section: Discussionsupporting
confidence: 92%
“…Although the C282Y mutation has a greater impact on iron balance than H63D, high intensity donors that carry the H63D mutation have decreased hepcidin to ferritin ratios when compared to those without the mutation (Mast et al , 2008a). A separate study found that the prevalence of H63D was higher among female than male donors (Konig et al , 2003). These data suggest that carriers of H63D may absorb more dietary iron when iron stores are depleted than those without the mutation, potentially protecting them from blood donation‐induced iron deficiency anaemia.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…This was somewhat surprising, since C282Y is more strongly associated with hemochromatosis . However, previous studies have found a protective association of H63D, but not C282Y, on iron status in frequent donors . For example, H63D is fourfold more prevalent in frequent Black donors than in first‐time Black donors .…”
Section: Discussionmentioning
confidence: 90%
“…28 However, previous studies have found a protective association of H63D, but not C282Y, on iron status in frequent donors. 29 For example, H63D is fourfold more prevalent in frequent Black donors than in first-time Black donors. 9 And, in a population of high-intensity donors, those with H63D had decreased hepcidin:ferritin ratio compared to those without this mutation.…”
Section: Discussionmentioning
confidence: 99%